Epidemics and ways to prevent and treat them in the North Africa in the modern period - Nadhir ROUABHI, Salah Eddine ZENNOU, Cheboub MOHAMMED, Youssouf DAHMANI, & Mustapha HALIMI (Akofena)
Abstract: This topic deals with the history of epidemics in the region North Africa In the modern period, by addressing the most important epidemic diseases that the modern Maghreb society suffered from, as well as studying and discovering the ways and mechanisms that enabled it to overcome these health ordeals, and to reach this scientific goal, we adhered to the historical, descriptive and analytical approach by defining and describing these diseases and clarifying their impact on human health, in addition to tracking the sources of these epidemics and trying to identify their causes. These epidemics that the Maghreb society knew had external causes in most cases as a result of its contact and interaction with its external environment, whether in the religious, commercial or even political framework. Accordingly, epidemics, in addition to being health phenomena, are fateful phenomena that determine the future of countries and peoples. Either they become aware and set off on their own to join the development bandwagon or they withdraw into themselves and decline, and thus they are exposed to all kinds of extortion.